Skin and bones : and other Mike Bowditch short stories - Doiron, Paul (New York : Minotaur Books, 2025)
"A collection of eight gripping original short stories in the bestselling Mike Bowditch series$1 (Bincluding one brand new, never-before-published story"s
The Bear trap -- Backtrack -- Rabid -- The Imposter -- Skin and bones -- The Caretaker -- Snakebite -- Sheep's clothing.
Maine author.
Keywords: Bowditch, Mike -- Fiction; Game wardens -- Fiction; Wilderness areas -- Maine -- Fiction; Maine -- Fiction; Detective and mystery fiction; Short stories